Planning in Shaping Students' Manners and Character in State High Schools - Muhammad Fikri Fathulloh; Wirdati Wirdati (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
The development of students' character and manners is an essential dimension of Islamic Religious Education (PAI) learning and requires systematic pedagogical design from the learning-planning stage. This study aims to analyze in depth the learning planning of PAI in shaping students' character at SMA Negeri 1 Sutera, West Sumatra Province. The research uses a qualitative approach with a case study design. The research participants were three PAI teachers who were directly involved in preparing learning-planning tools. Data were collected through in-depth interviews and documentation studies of teaching modules, learning goal flows, and attitude assessment planning tools. Data analysis is conducted using an interactive model that includes data reduction, data presentation, and the drawing of conclusions, accompanied by triangulation of sources and techniques to ensure data validity. The results of the study show that PAI learning planning explicitly and systematically integrates the values of manners into the formulation of learning objectives, the analysis of student needs, the preparation of teaching materials, the selection of learning methods and models, the planning of interactive learning activities, the allocation of time, and the evaluation of attitudes. All components of the planning are organized in accordance with the principles of the Independent Curriculum, with the development of character and manners as the primary goal of learning, rather than merely an indirect outcome. The novelty of this research lies in situating PAI learning planning as a moral design stage that is consciously and systematically directed toward the formation of students' character of manners, beyond its administrative function. These findings confirm that the quality of PAI learning planning plays a strategic role in deliberately and sustainably developing students' character.